Motivasi Masyarakat Terhadap Aktivitas Car Free Day di Alun-alun Kabupaten Temanggung (Indonesian Journal for Physical Education and Sport, 2022)
The purpose of this research to describe the community's motivation to sport activities In the Car Free Day Square of Temanggung district. The research method used Is a survey through a quantitative approach. Data collection Is done by observation, Interviews, and questionnaires. The results showed that the community's motivation to exercise due to physiological needs had a percentage of 23,3%, a safety requirement of 23,03%, a social need of 19.30%, the need for an award of 12,55%, and self-actualisation requirement of 21,49%. For the people of Temanggung distict,it is hoped that they can make as good as possible of Car Free Day activity because the Car Free Day is a means of self-actualization which is very beneficial for improving health, physical fitness, social and self-actualization. Then for the local government to expand the hygiene facilities such as trash cans and handwashing places and for organizers or community leaders still provide the best service so that the community Is Increasingly motivated to exercise In the Car Free Day of Temanggung District Square.